Overview of Magnetic Levitation Systems with Emphasis on Electrodynamic Suspension - Abbas Najjar-Khodabakhsh; Mohammad Reza Moradian; Bijan Moaveni (Journal of Intelligent Procedures in Electrical Technology, 2011)
Nowadays, the use of magnetic levitation systems has made attention in transportation. Suspension is caused by two magnetic fields in the near distance and thus the repulsion and attraction induced between them. In Iran, different types of magnetic systems and their applications, especially in the transportation system were not considered deeply and the features and specifications of each of these systems is not discussed yet. In this article we want to review past research and studies on the applications and the characteristics of these systems to fully express and we do compare them with each other. We also offer the laboratory equipment for study the behavior of magnetic suspension systems with emphasis on electrodynamic suspension.